Tarnishing Opponents, Polarizing Congress: The House Minority Party and the Construction of the Roll‐Call Record. Issue 4 (25th May 2016) - Egar, William T.
Abstract : Existing research on congressional parties tends to focus almost exclusively on the majority party. I argue that the inattention to the House minority party hampers our understanding of the construction of the roll‐call record and, consequently, our understanding of the sources of polarization in congressional voting. Employing an original data set of House members' requests for recorded votes between 1995 and 2010, I demonstrate that votes demanded by the minority party are disproportionately divisive and partisan and make Congress appear considerably more polarized based on commonly used measures. Moreover, minority‐requested votes make vulnerable members of the majority appear more partisan and ideologically extreme.